Research hotspots and trends of epigenetic therapy in oncology: a bibliometric analysis from 2004 to 2023 - Li, Sisi; Liang, Xinrui; Shao, Qing; Wang, Guanwen; Huang, Yuxin; Wen, Ping; Jiang, Dongping; Zeng, Xiaohua (Frontiers in Pharmacology, 2024)
Background: Epigenetics denotes heritable alterations in gene expression patterns independent of changes in DNA sequence. Epigenetic therapy seeks to reprogram malignant cells to a normal phenotype and has been extensively investigated in oncology. This study conducts a bibliometric analysis of epigenetic therapy in cancer, providing a comprehensive overview of current research, identifying trends, and highlighting key areas of investigation. Methods: Publications concerning epigenetic inhibitors in cancer spanning 2004 to 2023 were retrieved from the Web of Science Core Collection (WoSCC). Co-occurrence analysis using VOSviewer assessed current status and focal points. Evolutionary trends and bursts in the knowledge domain were analyzed using CiteSpace. Bibliometrix facilitated topic evolution and revealed trends in keywords. National, institutional, and author affiliations and collaborations were also examined. Results: A total of 2,153 articles and reviews on epigenetic therapy in oncology were identified, demonstrating a consistent upward trend over time. The United States (745 papers), University of Texas MD Anderson Cancer Center (57 papers), and Stephen B. Baylin (27 papers) emerged as the most productive country, institution, and author, respectively. Keyword co-occurrence analysis identified five primary clusters: tumor, DNA methylation, epigenetic therapy, expression, and immunotherapy. In the past five years, newly emerging themes with increased centrality and density include “drug resistance,” “immunotherapy,” and “combination therapy.” The most cited publication reviewed current understanding of potential causes of epigenetic diseases and proposed future therapeutic strategies. Conclusion: In the past two decades, the importance of epigenetic therapy in cancer research has become increasingly prominent. The United States occupies a key position in this field, while China, despite having published a large number of related papers, still has relatively limited influence. Current research focuses on the “combination therapy”of epigenetic drugs. Future studies should further explore the sequencing and scheduling of combination therapies, optimize trial designs and dosing regimens to improve clinical efficacy.